Pengaruh Metode SAVI pada Mata Pelajaran Fiqih untuk Meningkatkan Hasil Belajar Siswa Kelas III MI Nuurul Fallah Tangunan Puri Mojokerto (The Influence of Savi for Fiqih to Increase the Result of Learning for III Grade MI Nuurul Fallah Tangunan Puri Mojok - Arif Efendi; Yasinta Harma Nurery (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Savi is a combination learning system between Anti-Phisycal Movement in learning process. The purpose of the research is to know the influence of Savi Method for increasing of learning result for III grade MI Nuurul Fallah students Tangunan Puri Mojokerto. The research used a quantitive desemi with pretest-posttest control group approachment. The research population are 24 respondents MI Nuurul Fallah of III grade in criterias below a. Registered students inclusive in 2020-2021. b. Healthy respondents and undisabled. c. Fail class respondents. The sampling technique used purposive sampling. Data analysis used non parametric test comparison Wilcoxom signed rank test wit P value is 0,005 so H2 is refused and H1 is accepted, it could be cloncluded that there was increasement for the learning result of III grade MI Nuurul Fallah after being learn using savi. The savi method is effective to increase the result learning due to its interesting presentment including application online video learning system which can be applicated in learning process increasement easily.